Identifying the Dimensions of the Domestic Tourism Demand Model in Tehran - Afifi, Ramin; Razaghi Shirsavar, Hadi; Valikhani Dehaghani , Mashaallah; Ebrahimpour, Alireza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The dynamics of domestic tourism have gained prominence, especially in the wake of global disruptions such as the COVID-19 pandemic, which shifted travel preferences towards more localized experiences. This study aims to identify and analyze the dimensions of domestic tourism demand in Tehran, focusing on the motivations, barriers, preferences, and impacts of tourism within the city. The objective is to provide a comprehensive understanding that can inform policy and strategic planning to enhance Tehran’s appeal as a domestic tourist destination. Methodology: A qualitative research approach was employed, utilizing semi-structured interviews as the primary data collection method. The study targeted a purposive sample of local residents, domestic tourists, and professionals within the tourism sector in Tehran. Theoretical saturation guided the data collection process, ensuring a thorough exploration of themes. Data were analyzed through thematic analysis, allowing for the identification of key patterns, themes, and categories within the data. Findings: The study unveiled five main themes: Motivations for Domestic Tourism, Barriers to Domestic Tourism, Perceptions of Tehran as a Tourist Destination, Tourist Preferences and Behaviors, and the Impact of Domestic Tourism. Each theme comprised various categories with associated concepts, ranging from cultural interest, relaxation, and social connections to economic factors, safety concerns, and the broader economic, cultural, and social impacts of tourism. These findings underscore the complex interplay of factors influencing domestic tourism demand in Tehran. Conclusion: This research highlights the multifaceted nature of domestic tourism demand in Tehran, revealing a spectrum of motivations driving tourists, alongside significant barriers that need addressing. The study underscores the potential of domestic tourism as a catalyst for economic development, cultural preservation, and social cohesion in Tehran. By addressing identified barriers and leveraging the motivations and preferences of domestic tourists, Tehran can enhance its domestic tourism sector.